2016
DOI: 10.1590/1807-7692bar2016150007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nostalgia on Customer Loyalty to Brand Post-Merger / Acquisition

Abstract: The main objective of this study is to identify the effect of nostalgic feelings on consumer loyalty to the prevailing brand following the extinction of a brand in a merger/acquisition process. We also propose an explanatory model of the relationships between tests of relevant constructs. Based on a review and theoretical reflection on the constructs under study, this paper outlines a theoretical model in which attitudes in relation to both extinct and prevailing brands mediate the relationship between nostalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…This outcome shows that customer gender does not facilitate a greater sense of brand iconness specifically for females or for males. This understanding is in agreement with Toledo and Lopes’s (2016) results, which stated that as individuals progress through their life cycle phases, they are more likely to feel nostalgic, recollecting the bygone memories of their early life with strong emotions regardless of gender differences. Collectively, our results stress that nostalgic brand positioning (NBP) is the central driver of brand passion and brand authenticity for female customers more than for male customers, whereas the effects of NBP are equally essential for female and for male customers in leading to brand iconness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This outcome shows that customer gender does not facilitate a greater sense of brand iconness specifically for females or for males. This understanding is in agreement with Toledo and Lopes’s (2016) results, which stated that as individuals progress through their life cycle phases, they are more likely to feel nostalgic, recollecting the bygone memories of their early life with strong emotions regardless of gender differences. Collectively, our results stress that nostalgic brand positioning (NBP) is the central driver of brand passion and brand authenticity for female customers more than for male customers, whereas the effects of NBP are equally essential for female and for male customers in leading to brand iconness.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, surveys conducted by Li et al. (2019), Toledo and Lopes (2016) and Gilal et al. (2020) revealed that NBP can positively enhance consumers’ brand loyalty and willingness to pay, and also customers’ participation in brand resurrection movements.…”
Section: Introductionmentioning
confidence: 99%
“…Music products such as CDs or DVDs and official merchandise products are also targeted by fans to make purchases, as happened to the Indonesian music group, JKT48 (Andraini, 2019). Someone who has memories of good experiences for them also has a tendency to relive those experiences (Toledo & Lopes, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The research results of Jensen et al (2017) showed that brand nostalgia positively influences brand trust to a significant extent. Toledo and Lopes (2016) found that there is a positive/negative relationship between NE and attitude (e.g. BF/BI) in relation to the former brand/prevailing brand.…”
mentioning
confidence: 90%